Peningkatan Kemampuan Keterampilan Berbicara Dengan Metode Presentasi Pada Siswa SMP Darul Ulum Muncar - Ayu Pertiwi, Krisnanda (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
Skilled speaking requires students to be able to communicate with other students. Many students still have difficulty speaking in public. They may not even be confident in expressing ideas or opinions either in class or in public. Therefore, in Islamic religious education, students must be trained in public speaking skills and self-confidence. This can be achieved in schools by using the public speaking learning presentation method. To build public speaking skills and student self-confidence by using the presentation method in the Indonesian language learning process, support is needed from various school components, especially teachers in implementing learning in the classroom. 1. This study focuses on discussing presentations in building students' public speaking which focuses on How is the concept of presentation methods in learning Indonesian at SMP Darul Ulum Muncar? 2. How are Teachers' Efforts in building public speaking skills and students' self-confidence in learning Indonesian at SMP Darul Ulum Muncar? 3. How is the application of presentation methods to build public speaking and students' self-confidence in learning Indonesian at SMP Darul Ulum Muncar? The research method This research is a research (field research) or field research is an approach in research used to obtain concrete data in field research. The type of research used in this study is qualitative research. Qualitative research is a study aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people in the same direction as individuals or groups. Several descriptions are used to find principles and explain that lead to conclusions.